Effects of different recovery periods following a very intense interval training session on strength and explosive performance in elite female ice hockey players - Petré, H.; Tinmark, F.; Rosdahl, H.; Psilander, N. (The Journal of Strength and Conditioning Research, 2024)
This study investigates how different recovery periods after high-intensity interval training (HIIT) affects strength and explosive performance during a power training (PT) session. Fifteen female elite ice hockey players (22.5 ± 5.2 years) performed PT, including 6 sets of 2 repetitions (reps) of isometric leg press (ILP) and 6 sets of 3 reps of countermovement jump (CMJ), following a rested state and 10 minutes, 6 hours, or 24 hours after HIIT (3 sets of 8 × 20 seconds at 115% of power output at maximal oxygen consumption on a cycle ergometer). Peak force (PF) and peak rate of force development (pRFD) were measured during the ILP. Peak jump height (PJH), concentric phase duration (ConDur), eccentric phase duration, total duration, peak power (PP), velocity at peak power (V@PP), and force at peak power were measured during CMJ. The following variables were significantly reduced when only a 10-minute recovery period was allowed between HIIT and PT: PF was reduced by 7% (p < 0.001), pRFD by 17% (p < 0.001), PJH by 4% (p < 0.001), ConDur by 4% (p = 0.018), PP by 2% (p = 0.016), and V@PP by 2% (p = 0.007). None of the measured variables were reduced when PT was performed 6 and 24 hours after HIIT. We conclude that strength and explosive performance of elite female ice hockey players is reduced 10 minutes after HIIT but not negatively affected if a rest period of at least 6 hours is provided between HIIT and PT.